Pengaruh Konflik Kerja, Beban Kerja, dan Kepemimpinan Terhadap Kinerja Karyawan di Ria Busana Kediri - Rovianka Dwi Mayasari; Brahma Wahyu Kurniawan; Zulfa Rahmawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine the influence of work conflicts, workload, and leadership style on employee performance at Toko Ria Busana Kediri. The independent variables in this study include work conflict, workload, and leadership, while the dependent variable is employee performance. The research method used is a quantitative approach with multiple linear regression analysis. Data was obtained through the distribution of questionnaires to 30 employee respondents who work at Toko Ria Busana Kediri. The results of the study show that partially, work conflict and workload have a significant negative effect on employee performance. This means that the higher the level of conflict and the perceived workload, the lower employee performance tends to decrease. On the other hand, the leadership variable has a significant positive effect on performance, which means that a good leadership style is able to improve employee performance. Simultaneously, these three variables have a significant influence on employee performance.